2021
DOI: 10.1007/s00431-021-04169-x
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ pain and distress during peripheral intravenous cannulation in a paediatric emergency setting

Abstract: The objective of the study is to investigate pain and distress experienced by a group of adolescents and children during peripheral intravenous cannulation in a paediatric emergency department. This cross-sectional study was performed between November 2019 and June 2020 at the paediatric emergency department of the Institute for Maternal and Child Health of Trieste, Italy. Eligible subjects were patients between 4 and 17 years old undergoing intravenous cannulation, split into three groups based on their age: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…There was no significant difference in VAS scores between the ages of the children and within each age group. Giorgio Cozzi et al found in their study that adolescent patients had high levels of pre-procedural distress and comparable degrees of pain and anguish to younger patients [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference in VAS scores between the ages of the children and within each age group. Giorgio Cozzi et al found in their study that adolescent patients had high levels of pre-procedural distress and comparable degrees of pain and anguish to younger patients [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a broad consensus that medical routine procedures are not a pleasant experience. Blood sampling, one of the most common routine procedures, is associated with increased levels of anxiety and pain, especially when the patients undergoing venipunctures are children ( 1 3 ). This can lead to both immediate consequences, such as impeding timely diagnosis, and long-term effects, such as causing or intensifying medical avoidance due to traumatic experiences ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%